Notes on Chasmocarcinus latipes Rathbun, 1898 (Brachyura, Goneplacoidea, Chasmocarcinidae) from the Gulf of California, Mexico - Hendrickx, Michel E.; Hermoso-Salazar, Margarita (Zootaxa, 2018)
Brachyuran crabs from the Mexican Pacific and surrounding areas are well known and have been treated in several monographs (e.g., Garth 1958; Hendrickx 1997, 1999). Checklists of species occurring off western Mexico and the eastern tropical Pacific are also available (e.g., Hendrickx 1993, 1995, 2005). In many cases, particularly in species inhabiting the continental shelf or deeper waters, however, there is a significant lack of records due to sampling difficulty and cost.